The association between the neutrophil to lymphocyte ratio and in-hospital mortality among sepsis patients: A prospective study. Issue 30 (29th July 2022) - Chebl, Ralph Bou; Assaf, Mohamad; Kattouf, Nadim; Haidar, Saadeddine; Khamis, Mohamed; Abdeldaem, Karim; Makki, Maha; Tamim, Hani; Dagher, Gilbert Abou
Abstract : The Neutrophil to lymphocyte ratio (NLR) was shown to be associated with disease severity, poor prognosis and increased mortality in sepsis. However, the association between NLR and sepsis prognosis remains controversial. Our study aims to prospectively examine the prognostic ability of NLR in predicting in-hospital mortality among sepsis patients and determine the optimal cutoff of NLR that can most accurately predict in-hospital mortality in sepsis patients. This study was a prospective cohort study that included adult sepsis patients that presented to the emergency department of a tertiary care center between September 2018 and February 2021. Receiver operating characteristic curve was used to determine the optimal cutoff of the neutrophil to lymphocyte ratio that predicts in-hospital mortality. Patients were divided into 2 groups: above and below the optimal cutoff. Stepwise logistic regression was performed to assess the magnitude of the association between NLR and in-hospital mortality. A total of 865 patients were included in the study. The optimal cutoff for the neutrophil to lymphocyte ratio that predicts in-hospital mortality was found to be 14.20 with a sensitivity of 44.8% and a specificity of 65.3% (with PPV = 0.27 and NPV = 0.80). The area under the curve for the ratio was 0.552 with a 95% confidence intervals = [0.504–0.599] with a P value = .03. Patients that have a NLR above the cutoff were less likely to survive with time compared to patients below the cutoff based on the Kaplan–Meier curves. In the stepwise logistic regression, the optimal neutrophil to lymphocyte ratio cutoff was not associated with in-hospital mortality (odds ratios = 1.451, 95% confidence intervals = [0.927–2.270], P = .103). In conclusion the optimal cutoff of the NLR that predicts in-hospital mortality among sepsis patients was 14.20. There was no association between the NLR and in-hospital mortality in sepsis patients after adjusting for confounders. Further studies with a larger sample size should be done to determine the optimal NLR cutoff and its prognostic role in septic patients (in-hospital mortality and other clinically significant outcomes).